Resilience as a moderator of the effects of types of workplace bullying and job performance - Yu-Chia Chang; Shi-Ting Huang; Chih-Chun Wang; Cheng-Chia Yang (BMC Nursing)
Abstract Background Workplace bullying is a problem that can occur in any occupation or organization and is a stressful and negative experience for employees; resilience helps employees to better resist workplace bullying. The purpose of this study was to examine whether resilience moderates the effects of workplace bullying on job performance and to determine whether this moderating effect differs between three types of bullying: personal, work-related, and physical bullying. Methods A self-administered, paper-based questionnaire was distributed to full-time nurses at three regional hospitals in Taiwan. Cross-sectional data on workplace bullying behaviors, resilience and job performance were collected from 422 nurses using a questionnaire survey. Data were collected using the Job Performance Scale, the Negative Acts Questionnaire, and the Resilience Scale (CD-RISC-10), and the resulting data were analyzed using SPSS 21 and the PROCESS macro. Results Resilience moderated the positive relationship between personal, physical bullying and job performance (b = .11, p < .05; b = .17, p < .05), but did not moderate the effects of work-related bullying. Conclusions The findings of this study highlight the need for organizations to be proactive in preventing work-related bullying and to promote and enhance individual resilience. Managers need to be aware of the detrimental effects of work-related bullying, which can damage employees' physical and mental health and contribute to workplace toxicity.